2023
DOI: 10.3758/s13414-022-02640-x
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in frontoparietal activation for target and distractor singletons during visual search

Abstract: Age-related decline in visual search performance has been associated with different patterns of activation in frontoparietal regions using functional magnetic resonance imaging (fMRI), but whether these age-related effects represent specific influences of target and distractor processing is unclear. Therefore, we acquired event-related fMRI data from 68 healthy, communitydwelling adults ages 18-78 years, during both conjunction (T/F target among rotated Ts and Fs) and feature (T/F target among Os) search. Some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 141 publications
0
1
0
Order By: Relevance
“…Critically, the activation of the insula was not observed in older participants during the local processing, suggesting a salience network impairment with healthy aging. This finding is contrasting with the study by Merenstein et al [ 29 ] as the authors described age-related increases in activation in the insula during a visual search task (conjunction (T/F target letters among rotated Ts and Fs) > feature (T/F target letters among Os) contrast). Their diffusion decision analyses further suggested a significant mediation role of the insula activation in predicting an age-related decrease in the rate of evidence accumulation during the conjunction search.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Critically, the activation of the insula was not observed in older participants during the local processing, suggesting a salience network impairment with healthy aging. This finding is contrasting with the study by Merenstein et al [ 29 ] as the authors described age-related increases in activation in the insula during a visual search task (conjunction (T/F target letters among rotated Ts and Fs) > feature (T/F target letters among Os) contrast). Their diffusion decision analyses further suggested a significant mediation role of the insula activation in predicting an age-related decrease in the rate of evidence accumulation during the conjunction search.…”
Section: Discussioncontrasting
confidence: 99%
“…Importantly, in such a context, a bottom-up selection—indicated by the selection being determined by the feature properties present in the environment, regardless of top-down control [ 45 ]—is involved. However, as soon as the environment becomes more visually complex and involves top-down processing to select the correct target (i.e., local processing in presence of visual distractors), brain and behavioral differences appear with late adulthood (see also [ 29 ]), as discussed further below.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Magnetic resonance imaging (MRI) studies have found age-related increases in boundary separation to be associated with reduced striatal activity [as measured with the blood oxygen level dependent (BOLD) signal] [39] and with reduction in fractional anisotropy (a diffusion tensor imaging (DTI) based measurement of fiber directionality/coherence) in white matter connections between the striatum and the pre-Supplementary Motor Area (preSMA) [26] . Other studies have linked age-related increases in non-decision time [47] , [48] and in drift rate [51] to differences in the BOLD signal in fronto-parietal regions. These findings are consistent with evidence suggesting that reductions in fronto-parietal activity may underpin age-related slowing in simple and choice RT tasks and SAT [8] , [36] , [45] , [56] .…”
Section: Introductionmentioning
confidence: 99%